The practitioner's guide to POLCA : the production control system for high-mix, low-volume and custom products - Suri, Rajan (CRC Press, Taylor & Francis Group, 2018)
"POLCA (Paired-cell Overlapping Loops of Cards with Authorization) isa card-based visual control system that manages the flow of jobs through the shop floor: at each operation, it controls which job should be worked on next to meet delivery targets. POLCA ensures that upstream operations use their capacity effectively by working on jobs that are needed downstream, while at the same time preventing excessive work-in-process (WIP) build-ups when bottlenecks appear unexpectedly. POLCA is particularly suited to companies manufacturing high-mix, low-volume and customized products. Such companies struggle with long lead times, late deliveries, and daily expediting to meet delivery dates. ERP systems are not designed to deal with this highly variable environment, and add-on software such as Finite Capacity Scheduling systems can require complex installation. Also, the Kanban system does not work well with low-volume or custom production. POLCA has delivered impressive results in such environments. It does not require any complex software implementation: it can be used without an ERP system or it can seamlessly complement an existing ERP system. This book:Provides a step-by-step roadmap on how to implement POLCA; invaluable for both companies that wish to implement POLCA as well as consultants and academics advising such companies. Explains the concepts in practical and easy-to-understand terms by showing detailed shop-floor examples. Includes more than 100 illustrations for understanding how POLCA works as well as for elaborating on details of the implementation steps. Contains case studies written by company owners and executives documenting their POLCA implementation process and the results achieved in various industries in six countries."--Provided by publisher.